2015
DOI: 10.5194/hess-19-4427-2015
|View full text |Cite
|
Sign up to set email alerts
|

Determining the stable isotope composition of pore water from saturated and unsaturated zone core: improvements to the direct vapour equilibration laser spectrometry method

Abstract: Abstract.A method to measure the δ 2 H and δ 18 O composition of pore waters in saturated and unsaturated geologic core samples using direct vapour equilibration and laser spectrometry (DVE-LS) was first described in 2008, and has since been rapidly adopted. Here, we describe a number of important methodological improvements and limitations encountered in routine application of DVE-LS over several years. Generally, good comparative agreement, as well as accuracy, is obtained between core pore water isotopic da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 44 publications
2
95
1
Order By: Relevance
“…3, center). Since the in situ approach is based on the same principle as the equilibration bag method, its applicability on samples with low water content is supported by a recent study of Hendry et al (2015), who found that the measurement accuracy of their equilibration procedure could be improved by increasing the sample amount of low water content soils to increase the amount of water available for equilibration in the bag.…”
Section: Campaignmentioning
confidence: 74%
“…3, center). Since the in situ approach is based on the same principle as the equilibration bag method, its applicability on samples with low water content is supported by a recent study of Hendry et al (2015), who found that the measurement accuracy of their equilibration procedure could be improved by increasing the sample amount of low water content soils to increase the amount of water available for equilibration in the bag.…”
Section: Campaignmentioning
confidence: 74%
“…Ziploc® bags were evacuated, sealed and massaged to homogenize, placed inside a second Ziploc® bag, and stored to equilibrate prior to analysis. We followed protocols of Hendry et al (2015) and Wassenaar et al (2008), whereby the Ziploc® bags containing the soil samples were inflated with dry air, sealed, and allowed to equilibrate at room temperature for additional three days prior to water vapor isotope analysis.…”
Section: Direct Vapor Equilibration Methodsmentioning
confidence: 99%
“…Equilibrium techniques include: direct liquid-water-vapor equilibrium (e.g. Wassenaar et al, 2008;Hendry et al, 2015), in situ equilibration (Gaj et al, 2016;Garvelmann et al, 2012;Rothfuss et al, 2013Rothfuss et al, , 2015Volkmann and Weiler, 2014), Hepurging (Ignatev et al, 2013), and CO 2 -and H 2 -equilibration (Hsieh et al, 1998;Jusserand, 1980;Kelln et al, 2001;Koehler et al, 2000;McConville et al, 1999;Scrimgeour, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Potentially fractionating effects of interactions between soil water and surfaces of clay minerals (Oerter et al, 2014;Gaj et al, 2017a, b;Newberry et al, 2017) are of minor relevance for our study, since clay contents were low in the sampled soils (Table 1). We can further ensure that the sampled soil volumes always contained much more than 3 g of water as suggested by Hendry et al (2015).…”
Section: Sampling Design and Analysismentioning
confidence: 99%